De-escalation studies in HPV-positive oropharyngeal cancer: How should we proceed?. (December 2021) - Golusinski, Pawel; Corry, June; Poorten, Vincent Vander; Simo, Ricard; Sjögren, Elisabeth; Mäkitie, Antti; Kowalski, Luis Paulo; Langendijk, Johannes; Braakhuis, Boudewijn J.M.; Takes, Robert P.; Coca-Pelaz, Andrés; Rodrigo, Juan P.; et al.
Highlights: The worldwide incidence of HPVpositive oropharyngeal squamous cell carcinoma (OPSCC) i is constantly rising. Patients with OPSCC are younger, have less co-morbidities and have better prognosis. clinical trials try to identify potential treatment modifications, aiming to minimize treatment-related toxicities. Until now, the data do not support any modification in contemporary treatment protocols. Over decades, increasingly real-world evidence data from retrospective, observational studies is becoming available. Abstract: Human papilloma virus (HPV) is a well-established causative factor in a subset of squamous cell carcinomas of the head and neck (HNSCC). Although HPV can be detected in various anatomical subsites, HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) is the most common HPV-related malignancy of the head and neck, and its worldwide incidence is constantly rising. Patients with OPSCC are generally younger, have less co-morbidities and generally have better prognosis due to different biological mechanisms of carcinogenesis. These facts have generated hypotheses on potential treatment modifications, aiming to minimize treatment-related toxicities without compromising therapy efficacy. Numerous randomized clinical trials have been designed to verify this strategy and increasingly real-world evidence data from retrospective, observational studies is becoming available. Until now, the data do not support any modification in contemporary treatment protocols. In this narrative review, we outline recent data provided by both randomized controlled trials and real-world evidence of HPV-positive OPSCC in terms of clinical value. We critically analyze the potential value and drawbacks of the available data and highlight future research directions. This article was written by members and invitees of the International Head and Neck Scientific Group. (www.IHNSG.com )